2015
DOI: 10.1089/mdr.2014.0183
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Characterization of ST195 and ST365 Carbapenem-Resistant Acinetobacter baumannii Harboring blaOXA-23 in Guangzhou, China

Abstract: We investigated the distribution of resistance genes and the clonal relationships among carbapenem-resistant Acinetobacter baumannii isolates from the intensive care unit wards of two hospitals in Guangzhou, China. From 2012 to 2013, 57 A. baumannii isolates were obtained from blood cultures from two hospitals in Guangzhou. The antibiotic resistance profiles were determined by using the Vitek2 system and Etest strips. PCR was used to detect the genes encoding OXA-type carbapenemases and metallo-β-lactamases an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
11
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 29 publications
3
11
1
Order By: Relevance
“…In this study, ST195 was the most commonly observed ST, accounting for 24/52 (46.1%) of the isolates, follow by ST208. These Values are presented as the mean ± standard deviation; malignancy includes haematological malignancies and solid tumours; cardiac disease includes coronary artery disease, hypertensive heart disease, valvular disease and cardiomyopathy; renal disease includes chronic renal failure; neurological disease includes cerebral haemorrhage and cerebral infarction; PPIs proton pump inhibitor drugs findings are similar to the findings of Zhou et al [25], who found that ST195 accounted for 31/57 (54.4%) isolates. These data collectively suggest that ST195 is the most common ST and may serve as a severe epidemic marker in the Guangzhou area.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In this study, ST195 was the most commonly observed ST, accounting for 24/52 (46.1%) of the isolates, follow by ST208. These Values are presented as the mean ± standard deviation; malignancy includes haematological malignancies and solid tumours; cardiac disease includes coronary artery disease, hypertensive heart disease, valvular disease and cardiomyopathy; renal disease includes chronic renal failure; neurological disease includes cerebral haemorrhage and cerebral infarction; PPIs proton pump inhibitor drugs findings are similar to the findings of Zhou et al [25], who found that ST195 accounted for 31/57 (54.4%) isolates. These data collectively suggest that ST195 is the most common ST and may serve as a severe epidemic marker in the Guangzhou area.…”
Section: Discussionsupporting
confidence: 80%
“…The lack of ST92 detection may be due to the relatively small sample size in our study, which may not accurately represent the diversity and relative abundance of A. baumannii STs. However, some studies [1,5,25] have shown that ST195, ST208, ST365, and ST191 (but not ST92) are the most common STs discovered in different hospitals across China. In this study, ST195 was the most commonly observed ST, accounting for 24/52 (46.1%) of the isolates, follow by ST208.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a significantly increased positive rate was observed in the β-lactamase gene in strains subjected to drug induction, particularly OXA-23 (64.9%) and AmpC (91.9%). To our knowledge, OXA-23-producing A. baumannii was resistant to IPM (29)(30)(31)(32)(33)(34)(35)(36). AmpC enzyme was encoded by chromogene, and it's over expression could induce drug resistance towards penicillin and the third generation broad-spectrum cephalosporins, through hydrolysis.…”
Section: Discussionmentioning
confidence: 98%
“…All known STs have been reported in China, where ST92 was the main ST before 2010 (Ruan et al, 2013), and ST195 together with ST208 are currently the main STs (Zhou et al, 2015; Qu et al, 2016). In the present study, ST195 and ST208 were moderately common STs and ST368 was the dominant type.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the OXA-23 carriage rate in China is relatively high. Some investigations have shown that the prevalence reached over 90% in coastal areas (Ji et al, 2014; Zhou et al, 2015). Additionally, the prevalence of the OXA-23 gene varies among isolates with different STs.…”
Section: Discussionmentioning
confidence: 99%